Determination of sample stability for a broad panel of coagulation parameters and factor assays on the Cobas t 711 analyzer starting from fresh-never-frozen plasma - Hoffmann, Michael; Gottschalk, Norbert; Huber, Philipp; Scheling, Vanessa; von Allmen, Nicole; Hegel, J. Kolja (Frontiers in Molecular Biosciences, 2025)
BackgroundPreanalytical procedures can affect the accuracy of coagulation assay results. Recommended plasma storage temperatures and durations need to be defined for individual coagulation assays. Here, we evaluated the effect of commonly applied plasma storage conditions for a broad panel of 23 basic coagulation parameters as well as specialized factor assays developed for the Cobas® t 711 analyzer (Roche Diagnostics International Ltd., Rotkreuz, Switzerland).MethodsThis single-center, prospective, observational study used anonymized, residual, platelet-poor plasma samples as well as pseudonymized plasma samples to obtain rare ranges of certain analytes. Fresh-never-frozen plasma samples processed within 4 h were tested in triplicate at time zero (t0), with measurements repeated at various predefined timepoints after storage at 18–25°C, 2–8°C, or under freezing and deep freezing. Mean deviation from t0, expressed as a percentage or as absolute change in signal at very low analyte levels, was assessed against predefined, assay-specific acceptance criteria for each analyte.ResultsThe sample stability results under the examined storage conditions for all 23 assays met or exceeded the requirements for routine laboratory coagulation testing and the respective acceptance criteria for each individual assay were fulfilled. Fresh-never-frozen samples were used to reflect real-life laboratory settings, enabling the early detection of out-of-specification results.ConclusionSample stability was determined for a broad panel of assays on the t 711 analyzer, for application in routine coagulation testing practice.